Governance structures in Europe - WWWforEurope; Sachs, Andreas (Vienna, 2013)
"The policy report summarizes the research findings of Area 4. It is structured along milestone 80 (WWWforEurope Working Paper Number 4) which provides a broad perspective on governance in Europe. The additional milestones are grouped according to their focus in three groups which make up the distinct sections. The final section gives an outlook how the findings of the various milestones can be used as an input for the policy formulation phase of the project. A central shortcoming of existing governance structures is the weak integration of the (long-term) oriented Europe 2020 strategy in the (more short-term) oriented procedures summarized under the European Semester. A high level of heterogeneity in the EU, the possibility of spillovers caused by national policies, as well as the difficulty of specifying reform needs at the national level call for an adjustment of existing EU governance which is focused less on procedures and rules and more on a case- and country-specific treatment such that the actual needs at both the national and the EU level are taken into consideration."